1998
DOI: 10.1097/00007632-199801150-00008
|View full text |Cite
|
Sign up to set email alerts
|

Outcome Analysis of Noninstrumented Anterior Cervical Discectomy and Interbody Fusion in 348 Patients

Abstract: Results of this study indicate that better outcome in noninstrumented anterior cervical discectomy and fusion is associated with solid fusion, fewer fused levels, nonsmoking patients, higher education levels, and absence of secondary economic gain. There was no correlation between fusion status and bone graft source or use of cervical collar.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
87
1
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 214 publications
(96 citation statements)
references
References 7 publications
5
87
1
1
Order By: Relevance
“…Vavruch et al [27] found the clinical outcome for both treatment groups was the same. Their study and the above results are also comparable with other studies reviewing anterior cervical fusion procedures reporting symptomatic relief and patient satisfaction approaching 90% [10,22,25].…”
Section: Clinical Evaluationsupporting
confidence: 89%
See 1 more Smart Citation
“…Vavruch et al [27] found the clinical outcome for both treatment groups was the same. Their study and the above results are also comparable with other studies reviewing anterior cervical fusion procedures reporting symptomatic relief and patient satisfaction approaching 90% [10,22,25].…”
Section: Clinical Evaluationsupporting
confidence: 89%
“…This general technique has only undergone minor refinements over four decades with satisfactory clinical results from many trials at about 90% [10].…”
mentioning
confidence: 99%
“…Anterior corpectomy and resection of OPLL is a radical surgical option due to direct decompression, and provides satisfactory results. The overall fusion rate in a large number of patients evaluated in a comprehensive literature review was 92% [20]. In this study, we observed that the surgical approach was closely related with postoperative JOA score and IR.…”
Section: Discussionmentioning
confidence: 60%
“…The kyphotic alignment of the cervical spine and of the fused vertebrae is a commonly reported complication after the Cloward procedure. In a review of the extensive literature on the Cloward procedure, Chauten et al [8] reported a rate of kyphotic alignment of 20%. Vavruch et al [51] reported an increase of SSA at 1-year followup after the Cloward procedure.…”
Section: Discussionmentioning
confidence: 99%
“…1). This technique is reportedly associated with overall rates of satisfaction ranging from 70% to 99% depending on type of grading scale [8,12,34,36,41,46]. When one cervical segment is fused, the adjacent cervical levels provide compensatory motion, thus increasing the mechanical stress of these sites [9,18,20,25,33,39].…”
Section: Introductionmentioning
confidence: 99%